Língua inglesa na escola pública: uma nova perspectiva de abordagem - Viera, Paôla Rodrigues (2023)
Understanding the learning of an additional language as an enhancer of learning and the construction of the student as an active individual in society, this article turns its attention to relating multiliteracies and the teaching of the English Language. In that regard, it seeks to articulate, in a didactic sequence, precepts from multiliteracies to language practices proposed by Base Nacional Comum Curricular – BNCC (speaking, reading, writing, linguistics knowledge, and intercultural dimension) for English teaching. This is, therefore, exploratory research, which seeks to transpose theory into practice through the development of didactic activities. The research is mainly based on studies by Marzari e Gehres (2015), the New London Group (1966), Roxane Rojo (2012), Magda Soares (2002 – 2003), the Base Nacional Comum Curricular (2018).